ANALYSIS OF LEADING SECTORS: STUDY CASE IN MEDAN 2014-2018 - Ade L Banjarnahor; Esron Suryanto Hutagaol; Nancy Nopeline; Nisyopelin Nisyopelin; Krista Dwi Yora Hutasoit; Yedida Sinaga (Universitas Tidar, 2021)
The purpose of this research is to determine the leading economic sectors in Medan. This study uses secondary data in the form of time series (time series) from the Gross Regional Domestic Product (GRDP) of Medan. By using GDRP data, then it can be known which sector is prominent sector in that region. Some methods using GDRP data as a decisive prominent sector are Typology Klassen, LQ, and Shift Share. These methods classifying the economic sectors into four groups, they are prominent sector, based on large of contribution and rate of growth. By taking the study Medan area, then by used those methods can be known which sector be prominent Sector in Medan area. Based on the result from analysis methods, they are same result about prominent Sector: Water Supply, Waste Management, Waste and Recycling; Construction and Wholesale and Retail Trade; Car and Motorcycle repair, real estate, education services, health services and social activities, and other services.